Dysferlin at transverse tubules regulates Ca2+ homeostasis in skeletal muscle - Kerr, Jaclyn P.; Ward, Christopher W.; Bloch, Robert J. (Frontiers in Physiology, 2014)
The class of muscular dystrophies linked to the genetic ablation or mutation of dysferlin, including Limb Girdle Muscular Dystrophy 2B (LGMD2B) and Miyoshi Myopathy (MM), are late-onset degenerative diseases. In lieu of a genetic cure, treatments to prevent or slow the progression of dysferlinopathy are of the utmost importance. Recent advances in the study of dysferlinopathy have highlighted the necessity for the maintenance of calcium handling in altering or slowing the progression of muscular degeneration resulting from the loss of dysferlin. This review highlights new evidence for a role for dysferlin at the transverse (t-) tubule of striated muscle, where it is involved in maintaining t-tubule structure and function.